Industry-led corporate start-up accelerator design: Lessons learned in a maritime port complex - Garcia-Herrera,C; Perkmann,M; Childs,PRN (The Design Society, 2018)
Given the increasing disruption in every industry, firms can design new interfaces to further their strategic exploration efforts in order to remain competitive. Based on an inductive multi-case study research in a leading maritime port complex, we devised an actionable framework to design and run an industry-led accelerator through four steps: ecosystem orchestration, innovation funnel generation, flexible matching and scaling corporate start-up recurrent engagement. This framework can guide managerial practice and inform corporate start-up acceleration design in similar industrial contexts.